Development and evaluation of a CRISPR/Cas12a-based diagnostic test for rapid detection and genotyping of HR-HPV in clinical specimens - Lijuan Yin; Ziqian Zhao; Chunhua Wang; Caihong Zhou; Xiuzhen Wu; Baoxue Gao; Liangyuan Wang; Shuli Man; Xinkuan Cheng; Qiankun Wu; Siqi Hu; Hongxia Fan; et al. (Microbiology Spectrum)
ABSTRACT Persistent infection with high-risk human papillomavirus (HR-HPV) is the principal etiological factor of cervical cancer. Considering the gradual progression of cervical cancer, the early, rapid, sensitive, and specific identification of HPV, particularly HR-HPV types, is crucial in halting the advancement of the illness. Here, we established a rapid, highly sensitive, and specific HR-HPV detection platform, leveraging the CRISPR/Cas12a assay in conjunction with multienzyme isothermal rapid amplification. Our platform enables the detection and genotyping of 14 types of HR-HPV by using type-specific crRNAs. The outcomes of the detection can be interpreted either through a fluorescence reader or visually. Furthermore, we achieved one-tube multiplex detection of 14 HR-HPV types through the use of multiple amplifications and a crRNA pool. The detection sensitivity of this method is 2 copies/μL with no cross-reactivity, and the results can be obtained within 30 minutes. This method exhibited 100% clinical sensitivity and 100% clinical specificity when applied to 258 clinical specimens. Based on these findings, our CRISPR/Cas-based HR-HPV detection platform holds promise as a novel clinical detection tool, offering a visually intuitive and expedited alternative to existing HPV infection diagnostics and providing fresh perspectives for clinical cervical cancer screening.IMPORTANCEThis study developed a novel high-risk human papillomavirus (HR-HPV) detection platform based on CRISPR/Cas12a technology. This platform not only enables the rapid, highly sensitive, and specific detection and genotyping of 14 types of HR-HPV but also achieves single-tube multiplex detection of 14 HR-HPV types through ingenious design. The outcomes of the detection can be interpreted either through a fluorescence reader or visually. To the best of our knowledge, this is the first paper to utilize CRISPR/Cas diagnostic technology for the simultaneous detection of 14 types of HPV and to evaluate its feasibility in clinical sample detection using a large number of clinical samples. We hope that this work will facilitate the rapid and accurate detection of HPV and promote the broader application of CRISPR/Cas diagnostic technology.